2015
DOI: 10.1039/c5ra16680b
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of halogen bond and π–π interactions in thiophene-based building blocks

Abstract: The use of a thiophene-based building block (Pyr-T) to achieve a supramolecular assembly driven by halogen bonding (XB) is described. X-ray crystallography, NMR, Raman spectroscopy, and computational chemistry afford evidence of strong XB and π–π stacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Otheri ntermolecularf orces, such as p-type interactions, are known to compete with halogen bondingi nt he condensed phases [8,11] and are likely competing here with halogen bondingi nt hese solutions. Furthermore, as seen in Tables 1a nd 2, the j Dq j and rsvdW results of halogen-bonded complexesd isplay ac lear trend and track the increasing interaction strength.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Otheri ntermolecularf orces, such as p-type interactions, are known to compete with halogen bondingi nt he condensed phases [8,11] and are likely competing here with halogen bondingi nt hese solutions. Furthermore, as seen in Tables 1a nd 2, the j Dq j and rsvdW results of halogen-bonded complexesd isplay ac lear trend and track the increasing interaction strength.…”
Section: Discussionmentioning
confidence: 99%
“…Halogen-bondi nteractions with pyrimidine's nitrogen atoms shift normalm odes to higher energy and upfields hift 1 Ha nd 13 CNMR peaks in adjacent nuclei. [8,11] For example, we demonstrated that the crystal structures that result from using pyridyl thiophene-based donors exhibit strong halogen bond interactions, ranging from À7.5 to À8.7 kcal mol À1 , supplemented by other secondary interactions including pstacking interactions. The unexpected observation of vibrational red shifts and downfield 13 CNMR shifts in some complexes suggestst hat other intermolecular forces such as p interactions are competing with halogenb onding.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations